2020
DOI: 10.1007/s00401-020-02145-7
|View full text |Cite
|
Sign up to set email alerts
|

Mutated ATP10B increases Parkinson’s disease risk by compromising lysosomal glucosylceramide export

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative brain disease presenting with a variety of motor and non-motor symptoms, loss of midbrain dopaminergic neurons in the substantia nigra pars compacta and the occurrence of α-synucleinpositive Lewy bodies in surviving neurons. Here, we performed whole exome sequencing in 52 early-onset PD patients and identified 3 carriers of compound heterozygous mutations in the ATP10B P4-type ATPase gene. Genetic screening of a Belgian PD and dementia with Lewy bodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(89 citation statements)
references
References 117 publications
(158 reference statements)
3
65
0
Order By: Relevance
“…Dnf1 and Dnf2 share the same βsubunit, Lem3, and both transport PE, PC, and glucosylceramide. Their human homologues, ATP10A and ATP10D, are implicated in diabetes, obesity, myocardial infarction, atherosclerosis, and Parkinson's disease (Folmer et al, 2009;Martin et al, 2020;van der Mark et al, 2013). Here we report the cryo-EM structures of Dnf1-Lem3 in three different states (E1, E1P-ADP, and E2P) and Dnf2-Lem3 in five different states (E1, E1-ATP, E1P-ADP, E2P, and E2P-transition).…”
Section: Introductionmentioning
confidence: 96%
“…Dnf1 and Dnf2 share the same βsubunit, Lem3, and both transport PE, PC, and glucosylceramide. Their human homologues, ATP10A and ATP10D, are implicated in diabetes, obesity, myocardial infarction, atherosclerosis, and Parkinson's disease (Folmer et al, 2009;Martin et al, 2020;van der Mark et al, 2013). Here we report the cryo-EM structures of Dnf1-Lem3 in three different states (E1, E1P-ADP, and E2P) and Dnf2-Lem3 in five different states (E1, E1-ATP, E1P-ADP, E2P, and E2P-transition).…”
Section: Introductionmentioning
confidence: 96%
“…We recently identified compound heterozygous loss-offunction mutations in the ATPase class V type 10B (ATP10B) gene increasing risk for PD (Table 1) [213]. ATP10B mRNA is mainly expressed in the gastrointestinal track and the brain [213].…”
Section: Atp10bmentioning
confidence: 99%
“…The knowledge acquired from the protein products of identified causal genes and risk factors of PD and APS indicates that defects in vesicular transport pathways, endolysosomal dysfunction, impaired autophagy-lysosomal protein and organelle degradation pathways, α-synuclein aggregation and mitochondrial dysfunction play key roles in PD pathogenesis [2,29,121,236,371]. More recent advances have revealed that several parkinsonism associated genes regulate membrane dynamics wherein mutations cause lipid pathway alterations associated with lysosomal dysfunction [82,93,201,213]. Additionally, associations between parkinsonism and lysosomal storage disorders (LSDs), caused by disruption of lysosomal biogenesis or function, are emerging from genetic discoveries and clinical epidemiology [82,169].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GBA is the most common genetic risk factor of PD with 7-12% of PD patients carrying mono-or bi-allelic mutations in GBA and an estimated odds ratio of 5.4 [18,24,74,75]. More recently, new data showed that rare variants in VPS13C and ATP10B, implicated in sporadic earlyonset PD patient are mimicking recessive inheritance [17][18][19][20]. PD patient carriers of pathogenic mutations in SNCA or GBA have a higher risk of developing cognitive impairment and presenting a clinical phenotype of DLB [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Targeted approaches and genomewide association studies (GWAS) associated SNCA and GBA loci and APOE4 allele status with increased risk of developing DLB [24,25]. The knowledge acquired from the protein products of causal and risk genes provided valuable insights in disease mechanisms underlying LBD [3,17,33,44,78,117]. Nonetheless causal genes in families and risk genes in patient cohorts, represent only a minor fraction of the genetic etiology of LBD.…”
Section: Introductionmentioning
confidence: 99%